2017
DOI: 10.1017/s0007114517001581
|View full text |Cite
|
Sign up to set email alerts
|

Food-based diet quality score in relation to depressive symptoms in young and middle-aged Japanese women

Abstract: Only a few studies have focused on the association between overall diet, rather than intakes of individual nutrients or foods, and depressive symptoms in Japanese. This cross-sectional study examined associations between a diet quality score and depressive symptoms in 3963 young (age 18 years) and 3833 middle-aged (mean age 47·9 (sd 4·2) years) Japanese women. Dietary information was collected using a diet history questionnaire. A previously developed diet quality score was computed mainly based on the Japanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 59 publications
1
41
1
Order By: Relevance
“…The Food Guide score was significantly associated with intakes of grains, green and yellow vegetables, non-green and yellow vegetables, fruits, mushrooms, seaweeds, and milk and milk products, because the Food Guide score is calculated from the adherence to the Japanese Food Guide Spinning Top. This result is consistent with a previous cross-sectional study in terms of the significant associations between diet quality score and nutrient and food group intakes based on the DHQ [22]. In addition, another study reported that a higher diet quality score was significantly associated with higher intakes of cereals, vegetables, meat, fish, milk and milk products, and fruits, and lower energy intakes from confectioneries, sugar-sweetened beverages, and alcoholic beverages [24].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The Food Guide score was significantly associated with intakes of grains, green and yellow vegetables, non-green and yellow vegetables, fruits, mushrooms, seaweeds, and milk and milk products, because the Food Guide score is calculated from the adherence to the Japanese Food Guide Spinning Top. This result is consistent with a previous cross-sectional study in terms of the significant associations between diet quality score and nutrient and food group intakes based on the DHQ [22]. In addition, another study reported that a higher diet quality score was significantly associated with higher intakes of cereals, vegetables, meat, fish, milk and milk products, and fruits, and lower energy intakes from confectioneries, sugar-sweetened beverages, and alcoholic beverages [24].…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have been conducted using pre-defined methods, and some of the studies have indicated dietary patterns for an assessment of dietary quality based on adherence to the Japanese Food Guide Spinning Top [21,22,23,24]. The Japanese Food Guide Spinning Top was developed to help people implement the Dietary Guidelines for Japanese.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, Sakai et al examined the cross-sectional association between diet quality score, mainly based on the Japanese Food Guide Spinning Top, and depressive symptoms, and observed an inverse association between these variables among 3963 young (age 18 years) and 3833 middle-aged (mean age 47.9 years) women [9]. Although we observed no prospective association between dietary score and risk of depressive symptoms, the cross-sectional association was statistically significant, as in the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…The association of the adherence to the Japanese Food Guide Spinning Top with depressive symptoms is of much interest. A cross-sectional study among young and middleaged Japanese women reported that closer adherence to the Japanese guidelines was associated with a lower prevalence of depressive symptoms [9]. To date, however, no evidence has been obtained from prospective studies.…”
Section: Introductionmentioning
confidence: 99%